ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENAWARAN DAN PERMINTAAN BERAS DI PROVINSI RIAU - Partini '; Suardi Tarumun; Ermi Tety (PEKBIS, 2014)
The purpose of this research is to analyze the factors that affect the demand andsupply of rice in Riau Province. The data used is the panel data ..time series from2006 until 2010 and cross section from each district/city except Pekanbaru andKepulauan Meranti. The data analyzed used simultaneous equation 2SLS method.The research result showed that all structural equation models have signs in2accordance economic criteria. Determinant coefficient (R ) from 0.33 until 0.99 andF value from 5.38 until 3,320.10. The rice supply affacted by year end stock ofBulog, import and rice production. While the results of the structural equation are (1)The planted area affected by grain price, palm oil price and lagged of planted area,(2) The harvest area affected by planted area, intensification area, and laggedharvest area, (3) The grain price affected by rice marketing margin, the governmentprice purchase and price of rice retail, (4) Productivity affected by fertilizerapplication, grain price and lagged productivity, (5) Fertilzer application affected byintensification area, (6) Bulog procurement affected number of population andlagged Bulog procurement (7) Seller procurement affected by number of populationand rice demand (8) .. affected by price of rice retail and Bulog procurement (9)Price of rice retail affected by world price, grain price and lagged of price of riceretail (10) Rice demand affected by price of rice retail and number of population.Keywords : Rice, simultaneous, 2SLS